Applications of High-Resolution Borehole Electrical Images to Sedimentary and Stratigraphic Analysis - Sanggam Hutabarat (Ikatan Ahli Geologi Indonesia, 2000)
The recent introduction of high-resolution imaging techniques such as FMI has resulted in a breakthrough with a wide range of applications. Because the reservoir can now be more accurately imaged, it is possible to describe it in a greater detail as three-dimensional package of subsurface geological objects. It has been demonstrated that the high-resolution borehole electrical images bring fundamental information which, when integrated with conventional open-hole log, core, seismic and test/production data, contribute both qualitative and quantitative descriptions of reservoirs. This information may be used as input to a deterministic sedimentologic-stratigraphic modelling that can provide a more precise definition of reservoir volumes and reservoir petrophysical properties.